Forming method for improving density of fiber reinforced ceramic matrix composite

By combining the precision and solidification process of the front -drive body with the high -temperature pressure sintering process, and optimizing the design of the substrate, the problem of low density of silicon boron nicotya fiber reinforcement silicon and nicotin composite materials, realized the significant improvement of the material performance, and met the high -speed aircraft of high -speed aircraft. High performance requirements.

CN119371222AActive Publication Date: 2025-01-28CHINA TEST & CERTIFICATION INT GRP CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411659939.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-28
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

In the prior art, the density of silicon boron-nitrogen fiber-reinforced silicon boron-nitrogen composite material is low, resulting in poor material performance and cannot meet the high Mach number usage requirements of high-speed aircraft.

Method used

By combining the precision and solidification process of the front drive body with the high -temperature pressure sintering process, and the optimized design matrix, regulating the process parameters of different composite stages, solve the problem of uneven distribution of the substrate and internal defects of the material, increase the density of composite materials Essence

Benefits of technology

The density of composite materials was increased to about 70%, improved the mechanical properties, heat resistance and dielectric properties of the material, and met high -performance requirements for high -speed aircraft.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371222A_ABST
    Figure CN119371222A_ABST
Patent Text Reader

Abstract

The invention discloses a forming method for improving the density of a fiber-reinforced ceramic-based composite material, and belongs to the technical field of composite material preparation. According to the method, the specific precursor mixture is selected as an impregnation matrix material and then combined with a high-temperature pressure sintering process, process parameters of different composite stages are regulated and controlled, the problem that a matrix formed by cracking of polyborosilazane in an existing process is non-uniform in distribution is solved to the maximum extent, internal defects of the material are reduced, and the performance of the material is improved. The non-uniform degree and the density of the composite material are greatly improved, and the damage degree to the fibers is reduced by reducing the number of compounding times, so that the fibers can exert better reinforcing and toughening effects, the tensile property, the bending property and other mechanical properties of the composite material are effectively improved, and finally the high-performance silicon-boron-nitrogen fiber reinforced silicon-boron-nitrogen composite material can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite material preparation, in particular to a molding method for improving the density of a fiber-reinforced ceramic-based composite material. Background Art

[0002] With the development of various new aircraft towards higher Mach flight speeds and longer flight distances, higher requirements are placed on a series of properties such as high temperature resistance, wave transmission, and load-bearing in their wave-transmitting and heat-proof components. They are required to withstand greater loads and aerodynamic thermal shocks in more severe working environments, and the working temperature can reach above 1600°C, and meet the requirements of high wave transmission characteristics. Ceramic materials are often the preferred materials for high-temperature resistant and wave-transmitting components of aircraft in the aerospace field because of their good high temperature resistance, heat protection, high strength and excellent electrical properties. Among wave-transmitting materials, traditional quartz ceramic materials have a low operating temperature, and the long-term non-ablation temperature does not exceed 1000°C, which cannot meet the high Mach number requirements of high-speed aircraft. The electrical properties of alumina ceramics, such as dielectric constant and dielectric loss, are poor, and cannot meet the requirements of wave transmission of components in high temperature environments. Silicon nitride ceramics have excellent high temperature resistance and electrical properties, but the inherent brittleness and other shortcomings of ceramic materials limit their reliability.

[0003] Further research found that ceramic fiber reinforced ceramic matrix composites have greatly improved material reliability due to the fiber reinforcement and toughening effect, and stand out in the selection of high-temperature resistant and wave-transparent components. Among them, silicon boron nitrogen fiber reinforced silicon boron nitrogen composite materials have become ideal high-temperature resistant and wave-transparent ceramic materials for high-speed aircraft due to their excellent dielectric properties, outstanding high-temperature resistance and high mechanical reliability.

[0004] Silicon-boron-nitrogen fiber reinforced silicon-boron-nitrogen composite materials mainly refer to ceramic composite materials with silicon-boron-nitrogen fibers as reinforcing fibers and silicon-boron-nitrogen as the matrix. Further research on silicon-boron-nitrogen fibers found that silicon-boron-nitrogen fibers have the advantages of both Si3N4 and BN materials, and have excellent properties such as oxidation resistance, high-temperature strength and modulus retention, high-temperature wave transmission and ablation resistance. In addition, the addition of boron elements to silicon-boron-nitrogen materials improves the temperature resistance of the material, so that compared with silicon nitride fibers, its use temperature in an inert atmosphere can reach more than 1600°C, and the corresponding composite materials have good high-temperature mechanical properties, stable electrical properties and ablation resistance. Therefore, the silicon-boron-nitrogen composite material prepared by the silicon-boron-nitrogen matrix has good high-temperature resistance, stable electrical properties and ablation resistance, and is an ideal material for high-temperature resistant and wave-transparent components of future aircraft.

[0005] At present, due to the novelty of the material, there are few research reports on silicon-boron-nitrogen fiber reinforced silicon-boron-nitrogen composite materials. The survey found that this type of material is mainly prepared by the precursor impregnation pyrolysis (PIP) process. The process is to weave silicon-boron-nitrogen fibers into fiber preforms, and then fully immerse the preforms in polyborosilazane organic precursors. The preforms impregnated with the precursors are cross-linked and cured at a certain temperature, and then the preforms with the precursor solidified are placed in a high-temperature sintering furnace for high-temperature pyrolysis reaction treatment. The organic precursors are converted into ceramic matrix through pyrolysis reactions, and then the preforms are densified. Through repeated impregnation, curing and pyrolysis steps of ceramic precursors, silicon-boron-nitrogen fiber reinforced silicon-boron-nitrogen composite materials are finally prepared. For example, CN112010654A, CN104261850A, CN115636681A, etc.

[0006] The silicon-boron-nitrogen precursor (i.e., polyborosilazane) used in the PIP process is generally viscous and has poor fluidity, which results in uneven distribution of the precursor inside the fiber preform after it is immersed in the preform and solidified. What is more influential is that the ceramic yield of the precursor solidified material is not high (generally less than 60%), and small molecular gases will be released during the cracking process. The resulting pores will further reduce the density of the composite material, resulting in a single poor effect on the overall density improvement of the composite material. At present, due to the limitations of the process and precursors, this type of composite material can only be prepared by multiple impregnation and curing of the composite precursor. However, even so, the effect of improving the density of the composite material and the uniformity of the matrix is ​​still limited, and the porosity of the final product can still be as high as 50% or more. Multiple rounds of cracking and composite treatment will also reduce the strength of the fiber preform. In this case, the mechanical properties, heat resistance and dielectric properties of the composite material will be greatly reduced, so that it is impossible to obtain an ideal high-temperature resistant and wave-transmitting composite material.

[0007] In order to solve the technical problems in the preparation of silicon boron nitrogen fiber reinforced silicon boron nitrogen composites by the PIP process, multiple rounds of high-temperature cracking process aggravate fiber damage, low yield of polyborosilazane ceramics, poor internal uniformity of the matrix after cracking, resulting in low density and poor performance of the composite materials, it is necessary to innovatively design the composite process of silicon boron nitrogen fiber reinforced silicon boron nitrogen composites. Summary of the invention

[0008] In order to solve the technical problems existing in the prior art, the present invention provides a molding method for improving the density of fiber-reinforced ceramic-based composite materials. The present invention combines the precursor impregnation and curing process with the high-temperature pressure sintering process, and selects an optimized designed matrix to maximize the solution to the problem of uneven matrix distribution formed by the cracking of polyborosilazane in the existing process, reduce internal defects of the material, and increase the density of the composite material to about 70%.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0010] In one aspect, the present invention provides a molding method for improving the density of a fiber-reinforced ceramic matrix composite material, comprising:

[0011] (1) Preparation of silicon boron nitrogen fiber preform: placing a preform formed by weaving silicon boron nitrogen fibers into a mold required for impregnation; the weaving is three-dimensional weaving, and the volume content of the fiber in the fiber preform is 35-50%;

[0012] (2) Immersing the prepared precursor mixture into the mold in step (1) by vacuum suction, ensuring that the liquid level covers the surface of the fiber preform;

[0013] The precursor mixture is prepared by uniformly dispersing the powder in the polyborosilazane precursor, and the precursor mixture is composed of the following components in mass percentage: polyborosilazane 70-90wt%; powder 10-30%;

[0014] The powder is a mixture of silicon nitride powder, boron nitride powder and yttrium oxide powder, the mass ratio of the silicon nitride powder to the boron nitride powder is 1-2.2:1, the mass of the yttrium oxide powder is 10wt% of the total content of the powder; the particle size of the silicon nitride powder is 100-500nm, the particle size of the boron nitride powder is 0.8-2μm; the particle size of the yttrium oxide powder is 50-200nm;

[0015] (3) Then, the mold containing the silicon boron nitride fiber preform impregnated with the precursor mixture obtained in step (2) is placed in a hot pressing sintering furnace, the temperature is increased to 220-260° C., and the temperature is kept for 6-8 hours under a nitrogen atmosphere to ensure that the polyborosilazane in the precursor mixture is completely cured;

[0016] (4) Then, the mold in the hot pressing sintering furnace in step (3) is pressurized to an initial pressure of 0.5 MPa to ensure that the pressure head in the furnace is in contact with the sample. After 2 hours, the temperature is further increased to 700-800°C and kept at this temperature for 4-6 hours;

[0017] (5) The hot pressing sintering furnace in step (4) is then pressurized to ensure that the pressure applied to the mold reaches 40-60 MPa;

[0018] (6) The hot pressing sintering furnace in step (5) is then heated to 1300-1500°C after 2-3 hours, and kept at this temperature for 6-8 hours while maintaining the pressure. After the end of the heat preservation, the temperature is lowered to 1000°C and the pressure is released, and the pressure is released to normal pressure within 10 minutes;

[0019] (7) The hot pressing sintering furnace in step (6) is then cooled to below 100° C., the furnace is opened and a sample is taken to obtain a silicon-boron-nitrogen fiber reinforced silicon-boron-nitrogen composite material, thus completing the entire composite process.

[0020] On the other hand, the present invention also provides a ceramic fiber reinforced ceramic matrix composite material prepared by the above method.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention proposes a new densification molding composite process for silicon-boron-nitrogen fiber reinforced silicon-boron-nitrogen composite materials. The process innovatively combines the precursor impregnation and curing process with the high-temperature pressure sintering process, selects an optimized designed matrix, and regulates the process parameters of different composite stages to maximize the solution to the problem of uneven matrix distribution formed by the cracking of polyborosilazane in the existing process, reduce internal defects in the material, and increase the density of the composite material to about 70%. The number of composite times is reduced to reduce the degree of damage to the fiber, so that the fiber can exert a better reinforcement and toughening effect, effectively improve the tensile and bending mechanical properties of the composite material, and finally obtain a high-performance silicon-boron-nitrogen fiber reinforced silicon-boron-nitrogen composite material.

[0023] On the basis of reducing the number of compounding times, the present invention further improves the density of the composite material and the uniform distribution of the matrix, thereby obtaining a high-performance silicon-boron-nitrogen fiber-reinforced silicon-boron-nitrogen high-temperature resistant and wave-transmitting composite material.

[0024] The present invention prepares the silicon boron nitride fiber preform impregnated with a polyborosilazane precursor mixture by placing it into a high-temperature hot pressing sintering furnace for curing-cracking integrated sintering composite preparation. The fiber reinforcement and the matrix can complete the material composite through a single hot pressing sintering process. Compared with the traditional PIP process, it avoids the repeated impregnation process of the precursor, reduces the damage of multiple rounds of high-temperature cracking to the silicon boron nitride fiber, greatly shortens the production cycle, greatly reduces the production cost, and is more conducive to industrial production.

[0025] The impregnated material used in the present invention is a composite impregnated phase formed by mixing a polyborosilazane precursor and a silicon nitride powder, a boron nitride powder matrix, and an yttrium oxide sintering aid. The yield of a single polyborosilazane ceramic is low, and a large amount of mass loss will occur during the cracking and compounding process, thereby generating a large number of pore defects after a single compounding. Adding silicon nitride powder and boron nitride powder to the impregnated material can greatly improve the impregnation efficiency and impregnation weight gain, reduce the pore content generated during the cracking of the precursor, and effectively improve the final density of the composite material. Compared with the single polyborosilazane precursor impregnation composite, the impregnation efficiency is increased by more than 40% by impregnation with a mixture of polyborosilazane, silicon nitride powder and boron nitride powder, and the final density of the material is increased by 30-50%. In addition, in the presence of yttrium oxide sintering aid, the sintering temperature of silicon nitride and boron nitride powders can be significantly reduced, thereby obtaining a sintered dense silicon boron nitride matrix at a relatively low temperature in the range of 1300-1500°C without damaging the silicon boron nitride fiber.

[0026] The sintering process proposed in the present invention is an innovatively designed process. Compared with the traditional hot pressing sintering process, the process link proposed in the present invention has obvious innovation. In a hot pressing sintering furnace, the precursor is first cured and formed at 220-260°C, and then the temperature is directly raised to 700-800°C in the furnace. At this temperature, the polyborosilazane precursor solidified material will begin to crack and form a powdered silicon boron nitrogen matrix. At this time, the pressurization operation is performed. Since the fiber preform is an integral structure, it can still ensure its own integrity under high pressure, and the powder matrix formed by the initial cracking will produce a certain fluidity under high pressure, so that the powder matrix will be evenly and fully diffused into the complete silicon boron nitrogen fiber preform, reducing the number and size of pore defects inside the composite material, and maximizing the solution to the problem of uneven distribution of the matrix formed by the cracking of polyborosilazane in the existing PIP process. When the temperature continues to rise to 1300-1500°C, under the action of pressure, the product after curing of borosilazane continues to decompose into powder and flow evenly into the preform, and under the action of high temperature and high pressure, silicon nitride powder and boron nitride powder will form silicon-boron-nitrogen composite ceramics, and due to the presence of yttrium oxide sintering aid, the densification sintering of silicon-boron-nitrogen composite ceramics will be further promoted to complete the composite densification process, and the sintering temperature is lower than 1500°C, which will not affect the state and performance of the silicon-boron-nitrogen fiber itself. Finally, under the promotion of the new preparation process proposed by the present invention, the internal uniformity and density of the composite material are effectively improved, and the comprehensive properties of the composite material such as mechanical properties and heat resistance are greatly improved, and finally the smooth preparation of high-performance silicon-boron-nitrogen fiber-reinforced silicon-boron-nitrogen high-temperature resistant wave-transparent composite material is realized. This process is an innovative design based on this type of material, aiming at the technical difficulties of low density, poor internal uniformity and low strength of composite materials in the PIP process.

[0027] At the same time, the new composite method in the composite material preparation process involved in the present invention has a relatively simple process, is easy to operate and easy to master, and has no stringent requirements on equipment. The present invention greatly improves the feasibility of industrial preparation of silicon-boron-nitrogen fiber-reinforced silicon-boron-nitrogen composite materials, effectively improves the density, force, heat and other comprehensive properties of the composite materials, and has a promoting significance for the subsequent development of silicon-boron-nitrogen fiber-reinforced silicon-boron-nitrogen composite materials and high-temperature resistant and wave-transparent materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a CT detection image after the flat plate component is composited in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] In order to make the technical problems to be solved, technical solutions and advantages of the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0030] In the present invention, the materials used can be obtained from commercial sources unless otherwise specified.

[0031] The present invention provides a molding method for improving the density of fiber-reinforced ceramic-based composite materials, and specific embodiments are as follows.

[0032] Example 1

[0033] A molding method for improving the density of a fiber-reinforced ceramic matrix composite material, comprising:

[0034] (1) Processing silicon boron nitrogen fiber into a fiber preform with a fiber volume content of 41% by three-dimensional weaving;

[0035] (2) Weighing 700 g of polyborosilazane, 180 g of silicon nitride powder, 90 g of boron nitride powder and 30 g of yttrium oxide powder, and mixing them thoroughly by ball milling to prepare an impregnation mixture of polyborosilazane (70 wt %), silicon nitride powder, boron nitride powder and yttrium oxide powder; then vacuuming the prepared mixed impregnation material into the mold containing the fiber preform in step (1), ensuring that the liquid level covers the upper surface of the fiber preform;

[0036] (3) Then, the mold containing the silicon boron nitride fiber preform impregnated with the precursor mixture obtained in step (2) is placed in a hot pressing sintering furnace, the temperature is increased to 220° C., and the temperature is kept for 6 hours under a nitrogen atmosphere to ensure that the polyborosilazane in the precursor mixture is completely cured;

[0037] (4) Then, the mold in the hot pressing sintering furnace in step (3) was pressurized to give an initial pressure of 0.5 MPa, ensuring that the pressure head was in contact with the sample, and maintained for 2 hours, and then continued to heat up to 700 ° C and kept at this temperature for 4 hours;

[0038] (5) Then, the mold in the hot pressing sintering furnace in step (4) is pressurized to 40 MPa;

[0039] (6) The hot pressing sintering furnace in step (5) is then heated to 1300°C in 2 hours, kept at this temperature for 6 hours, and maintained at a pressure of 40 MPa, and then cooled to 1000°C and depressurized to normal pressure within 10 minutes;

[0040] (7) Then, the hot pressing sintering furnace in step (6) was cooled to 80°C and the furnace was opened for sampling.

[0041] Example 2

[0042] A molding method for improving the density of a fiber-reinforced ceramic matrix composite material, comprising:

[0043] (1) Processing silicon boron nitrogen fiber into a fiber preform with a fiber volume content of 41% by three-dimensional weaving;

[0044] (2) Weighing 800 g of polyborosilazane, 90 g of silicon nitride powder, 90 g of boron nitride powder and 20 g of yttrium oxide powder, and mixing them thoroughly by ball milling to prepare an impregnation mixture of polyborosilazane (80 wt %), silicon nitride powder, boron nitride powder and yttrium oxide powder; then vacuuming the prepared mixed impregnation material into the mold containing the fiber preform in step (1), ensuring that the liquid level covers the upper surface of the fiber preform;

[0045] (3) Then, the mold containing the silicon boron nitride fiber preform impregnated with the precursor mixture obtained in step (2) is placed in a hot pressing sintering furnace, the temperature is increased to 260° C., and the temperature is kept for 8 hours under a nitrogen atmosphere to ensure that the polyborosilazane in the precursor mixture is completely cured;

[0046] (4) Then, the mold in the hot pressing sintering furnace in step (3) was pressurized to give an initial pressure of 0.5 MPa, ensuring that the pressure head was in contact with the sample, and maintained for 2 hours, and then continued to heat up to 800 ° C and kept at this temperature for 6 hours;

[0047] (5) Then, the mold in the hot pressing sintering furnace in step (4) is pressurized to 60 MPa;

[0048] (6) The hot pressing sintering furnace in step (5) is then heated to 1500°C in 2 hours, kept at this temperature for 8 hours, and maintained at a pressure of 60 MPa, and then cooled to 1000°C and depressurized to normal pressure within 10 minutes;

[0049] (7) The hot pressing sintering furnace in step (6) is then cooled to 90°C and the furnace is opened for sampling.

[0050] Example 3

[0051] A molding method for improving the density of a fiber-reinforced ceramic matrix composite material, comprising:

[0052] (1) Processing silicon boron nitrogen fiber into a fiber preform with a fiber volume content of 41% by three-dimensional weaving;

[0053] (2) Weighing 900 g of polyborosilazane, 45 g of silicon nitride powder, 45 g of boron nitride powder and 10 g of yttrium oxide powder, and mixing them thoroughly by ball milling to prepare an impregnation mixture of polyborosilazane precursor (90 wt %), silicon nitride powder, boron nitride powder and yttrium oxide powder; then vacuuming the prepared mixed impregnation material into the mold containing the fiber preform in step (1), ensuring that the liquid level covers the upper surface of the fiber preform;

[0054] (3) Then, the mold containing the silicon boron nitride fiber preform impregnated with the precursor mixture obtained in step (2) is placed in a hot pressing sintering furnace, the temperature is raised to 230° C., and the temperature is kept for 7 hours under a nitrogen atmosphere to ensure that the polyborosilazane in the precursor mixture is completely cured;

[0055] (4) Then, the mold in the hot pressing sintering furnace in step (3) was pressurized to give an initial pressure of 0.5 MPa, ensuring that the pressure head was in contact with the sample, and maintained for 2 hours, and then continued to heat up to 750 ° C and kept at this temperature for 5 hours;

[0056] (5) Subsequently, the mold in the hot pressing sintering furnace in step (4) is pressurized to 50 MPa;

[0057] (6) The hot pressing sintering furnace in step (5) is then heated to 1400°C in 2 hours, kept at this temperature for 7 hours, and maintained at a pressure of 50 MPa, and then cooled to 1000°C and depressurized to normal pressure within 10 minutes;

[0058] (7) The hot pressing sintering furnace in step (6) was then cooled to 70°C and the furnace was opened for sampling.

[0059] Example 4

[0060] In step (2) of this embodiment, the precursor mixture is: 700 g of polyborosilazane, 185.6 g of silicon nitride powder, 84.4 g of boron nitride powder and 30 g of yttrium oxide powder, and the other conditions are the same as those in embodiment 1.

[0061] In order to further illustrate the beneficial effects of the present invention, the following comparative example was constructed.

[0062] Comparative Example 1

[0063] A method for preparing a ceramic fiber reinforced ceramic matrix composite material, comprising:

[0064] (1) Processing silicon boron nitrogen fiber into a fiber preform with a fiber volume content of 41% by three-dimensional weaving;

[0065] (2) impregnating the fiber preform with the polyborosilazane precursor by vacuum inhalation impregnation, raising the temperature of the mold containing the fiber preform fully impregnated with polyborosilazane to 220° C., and keeping the temperature for 6 hours under a nitrogen atmosphere to ensure that the precursor is completely cured;

[0066] (3) The fiber preform with the polyborosilazane cured product in step (2) is then taken out, placed in a high-temperature cracking furnace, treated in an ammonia atmosphere at 1300° C. for 6 hours, and taken out after cooling. At this time, a complete polyborosilazane impregnation-curing-cracking process is completed;

[0067] (4) Steps (2) and (3) are then repeated. After the fifth compounding process is completed, the compounding weight gain is 3.3 wt%, and the compounding is completed;

[0068] The raw materials and pyrolysis process temperature parameters used in Comparative Example 1 for preparing ceramic fiber reinforced ceramic matrix composites are similar to those in Example 1, while Comparative Example 1 adopts the traditional PIP composite process, and the impregnated material is a single polyborosilazane precursor, and the number of composites is increased by 4 times compared with Example 1.

[0069] Comparative Example 2

[0070] A method for preparing a ceramic fiber reinforced ceramic matrix composite material, comprising:

[0071] (1) Processing silicon boron nitrogen fiber into a fiber preform with a fiber volume content of 41% by three-dimensional weaving;

[0072] (2) impregnating the fiber preform with the polyborosilazane precursor by vacuum inhalation impregnation, raising the temperature of the mold containing the fiber preform fully impregnated with polyborosilazane to 260° C., and keeping the temperature for 8 hours under a nitrogen atmosphere to ensure that the precursor is completely cured;

[0073] (3) The fiber preform with the polyborosilazane cured product in step (2) is then taken out, placed in a high-temperature cracking furnace, treated in an ammonia atmosphere at 1500° C. for 8 hours, and taken out after cooling. At this time, a complete polyborosilazane impregnation-curing-cracking process is completed;

[0074] (4) Steps (2) and (3) are then repeated. After the sixth compounding process is completed, the compounding weight gain is 1.6 wt%, and the compounding is completed;

[0075] The raw materials and pyrolysis process temperature parameters for preparing ceramic fiber reinforced ceramic matrix composites used in Comparative Example 2 are similar to those in Example 2, while Comparative Example 2 adopts the traditional PIP composite process, and the impregnated material is a single polyborosilazane precursor, and the number of composites is increased by 5 times compared with Example 2.

[0076] Comparative Example 3

[0077] A method for preparing a ceramic fiber reinforced ceramic matrix composite material, comprising:

[0078] (1) Processing silicon boron nitrogen fiber into a fiber preform with a fiber volume content of 41% by three-dimensional weaving;

[0079] (2) impregnating the fiber preform with the polyborosilazane precursor by vacuum inhalation impregnation, raising the temperature of the mold containing the fiber preform fully impregnated with polyborosilazane to 230° C., and keeping the temperature for 7 hours under a nitrogen atmosphere to ensure that the precursor is completely cured;

[0080] (3) The fiber preform with the polyborosilazane cured product in step (2) is then taken out, placed in a high-temperature cracking furnace, treated in an ammonia atmosphere at 1400° C. for 7 hours, and taken out after cooling. At this time, a complete polyborosilazane impregnation-curing-cracking process is completed;

[0081] (4) Steps (2) and (3) are then repeated. After the fifth compounding process is completed, the compounding weight gain is 2.7 wt%, and the compounding is completed;

[0082] The raw materials and pyrolysis process temperature parameters for preparing ceramic fiber reinforced ceramic matrix composites used in Comparative Example 3 are similar to those in Example 3, while Comparative Example 3 adopts the traditional PIP composite process, and the impregnated material is a single polyborosilazane precursor, and the number of composites is increased by 4 times compared with Example 3.

[0083] Comparative Example 4

[0084] A method for preparing a ceramic fiber reinforced ceramic matrix composite material, comprising:

[0085] (1)-(3) Same as Example 1;

[0086] (4) The fiber preform with the polyborosilazane cured product in step (3) is then taken out, placed in a high-temperature cracking furnace, treated in an ammonia atmosphere at 1300° C. for 6 hours, and taken out after cooling. At this time, a complete polyborosilazane impregnation-curing-cracking process is completed, and the composite is completed.

[0087] Comparative Example 5

[0088] The precursor mixture of this comparative example includes 600 g of polyborosilazane, 240 g of silicon nitride powder, 120 g of boron nitride powder and 40 g of yttrium oxide powder, and the other conditions are the same as those in Example 1.

[0089] Comparative Example 6

[0090] In the precursor mixture of this comparative example, silicon nitride powder was omitted, and other conditions were the same as those of Example 1.

[0091] Comparative Example 7

[0092] In the precursor mixture of this comparative example, yttrium oxide powder was omitted, and the other conditions were the same as those of Example 1.

[0093] Comparative Example 8

[0094] In the precursor mixture of this comparative example, silicon nitride powder was replaced with an equal amount of boron nitride powder, and the other conditions were the same as those of Example 1.

[0095] Comparative Example 9

[0096] In the precursor mixture of this comparative example, the boron nitride powder was replaced with an equal amount of silicon nitride powder, and the other conditions were the same as those of Example 1.

[0097] Comparative Example 10

[0098] In step (2) of this comparative example, the precursor mixture is: 700 g of polyborosilazane, 90 g of silicon nitride powder, 180 g of boron nitride powder and 30 g of yttrium oxide powder, and the other conditions are the same as those in Example 1.

[0099] Comparative Example 11

[0100] A method for preparing a ceramic fiber reinforced ceramic matrix composite material, comprising:

[0101] (1)-(3) Same as Example 1;

[0102] (4) Subsequently, the mold in the hot pressing sintering furnace in step (3) is pressurized to 40 MPa;

[0103] (5) The hot pressing sintering furnace in step (4) is then heated to 1300°C in 2 hours, kept at this temperature for 6 hours, and maintained at a pressure of 40 MPa, and then cooled to 1000°C and depressurized to normal pressure within 10 minutes;

[0104] (6) The hot pressing sintering furnace in step (5) is then cooled to 80°C and the furnace is opened for sampling.

[0105] Comparative Example 12

[0106] A method for preparing a ceramic fiber reinforced ceramic matrix composite material, comprising:

[0107] (1)-(4) Same as Example 1;

[0108] (5) The hot pressing sintering furnace in step (4) is then heated to 1300° C. over 2 hours, kept at this temperature for 6 hours, and then depressurized to normal pressure after the end of the heat preservation;

[0109] (6) The hot pressing sintering furnace in step (5) is then cooled to 80°C and the furnace is opened for sampling.

[0110] The inventors conducted performance tests on the materials prepared in the above embodiments and comparative examples. The test standards were based on "GJB873-2015 Test Method for Tensile Properties of Continuous Fiber-Reinforced Advanced Ceramic Composites at Room Temperature" and "ASTM C1341-2006 Standard Test Method for Flexural Properties of Continuous Fiber-Reinforced Advanced Ceramic Composites". The results are shown in Figure 1 and Table 1-2.

[0111] Table 1

[0112]

[0113] As can be seen from Table 1, the density of the composite material prepared by the method of the present invention is increased by more than 10% compared with the conventional impregnation-cracking method, and the tensile strength and flexural strength are increased by more than 35% and more than 18% respectively. The composite material obtained by the method of the present invention is tested by CT, and the internal structure of the material is relatively uniform and dense. The internal structure of the composite material obtained in Comparative Examples 1-3 is uneven, and the density is poor.

[0114] The present invention prepares a silicon boron nitrogen fiber preform soaked with a precursor mixture by placing it into a high-temperature hot-pressing sintering furnace for curing-cracking integrated sintering composite preparation. The fiber reinforcement phase and the matrix can be composited through a single sintering process. Compared with the traditional PIP process, the material production cycle is greatly shortened, the production cost is reduced, and the reduction in the number of material composites reduces the damage to the fiber reinforcement phase. Under the combined effect, the mechanical properties such as tensile strength and bending strength of the composite material are greatly improved, and the preparation of high-performance silicon boron nitrogen fiber reinforced silicon boron nitrogen high-temperature resistant wave-transparent composite materials is realized, which is of great significance for the subsequent development of high-temperature resistant wave-transparent materials.

[0115] Table 2

[0116]

[0117] As can be seen from Table 2, in Comparative Example 4, only the powder is added to improve the single impregnation composite efficiency, but it has little effect on the density, tensile strength and flexural strength of the composite material. In Comparative Example 5, there is too much powder and the viscosity of the precursor mixture is relatively high, resulting in a small amount of matrix immersed in the preform during the impregnation process, resulting in a poor single-composite densification effect, and the viscosity is too high, resulting in a very uneven distribution of the matrix inside the preform. In Comparative Example 6, without adding silicon nitride powder, the composite material obtained by single compounding has a low degree of densification and poor mechanical properties. In Comparative Example 7, the sintering aid is omitted, the powder has a low degree of densification at low temperature, the density is slightly lower than that of Example 1, and the flexural strength is also significantly reduced. In Comparative Example 8, silicon nitride powder is replaced with boron nitride powder. The sintering temperature of pure boron nitride is too high, and the composite material prepared under the conditions of Comparative Example 8 has a low degree of densification. In comparative example 9, the boron nitride powder is replaced with silicon nitride powder. Without the presence of boron nitride, silicon nitride and boron nitride cannot form a silicon-boron-nitrogen matrix, which has little effect on density and room temperature performance, but the lack of the addition of boron element affects the temperature resistance of the material, so the performance of the material is reduced under high temperature environment. In comparative example 10, the amount of each substance in the powder is changed, resulting in an excess of boron nitride. After the silicon-boron-nitrogen matrix is ​​formed, the remaining boron nitride has a low density. In comparative example 11, the prepolymer remains in a solid state after curing, and has high brittleness. When it is not cracked into powder, high pressure is directly applied, and cracking will occur. During the cracking process, the fiber preform will be pulled apart, resulting in a sharp drop in tensile strength. However, since the internal matrix content does not change much, the density is acceptable and has a certain bending strength, but the uniformity is very poor. Comparative example 12 omits the high pressure process. At this time, the pressure has little help for the fluidity of the powder after cracking, resulting in low matrix composite efficiency and low internal uneven density.

[0118] In summary, the present invention combines the precursor impregnation and curing process with the high-temperature pressure sintering process, selects an optimized impregnation matrix material, and adjusts the process parameters of different composite stages according to the characteristics of the matrix material, thereby maximally solving the problem of uneven matrix distribution formed by the cracking of polyborosilazane in the existing process, reducing internal defects in the material, and greatly improving the unevenness and density of the composite material.

[0119] The above is a preferred embodiment of the present invention. For ordinary technicians in this technical field, making several improvements and modifications without departing from the principles of the present invention should also be regarded as within the protection scope of the present invention.

Claims

1. A molding method for improving the density of a fiber-reinforced ceramic matrix composite material, characterized in that: include: (1) placing a fiber preform formed by weaving silicon-boron-nitrogen fibers into a mold required for impregnation; (2) Adding the precursor mixture into the mold in step (1) to ensure that the liquid level covers the upper surface of the fiber preform; The precursor mixture consists of the following components in percentage by weight: 70-90 wt % polyborosilazane; 10-30wt% of powder; the powder is a mixture of silicon nitride powder, boron nitride powder and yttrium oxide powder, the mass ratio of silicon nitride powder to boron nitride powder is 1-2.2:1, and the mass of yttrium oxide powder is 10wt% of the total content of the powder; (3) Then, the mold in step (2) is placed in a hot pressing sintering furnace, and the temperature is increased to completely solidify the precursor mixture; (4) The mold in the hot pressing sintering furnace of step (3) is then pressurized at a pressure of 0.5 MPa for 2 hours, and then the temperature is further increased to 700-800°C and kept at this temperature for 4-6 hours; (5) The hot pressing sintering furnace in step (4) is then pressurized to ensure that the pressure applied to the mold reaches 40-60 MPa; (6) The hot pressing sintering furnace in step (5) is then heated to 1300-1500°C within 2-3 hours, the pressure is maintained for 6-8 hours, and then the temperature is reduced to 1000°C and the pressure is released to normal pressure within 10 minutes; (7) The hot pressing sintering furnace in step (6) is then cooled to below 100° C., the furnace is opened and samples are taken to obtain a silicon-boron-nitrogen fiber reinforced silicon-boron-nitrogen composite material.

2. The method according to claim 1, characterized in that In the step (1), the weaving is three-dimensional weaving, and the volume content of the fiber in the fiber preform is 35-50%.

3. The method according to claim 2, characterized in that The particle size of the silicon nitride powder is 100-500nm, the particle size of the boron nitride powder is 0.8-2μm; and the particle size of the yttrium oxide powder is 50-200nm.

4. The method according to claim 1, characterized in that: In the step (3), the temperature is 220-260° C. and the temperature is kept at 6-8 hours under a nitrogen atmosphere.

5. A fiber-reinforced ceramic matrix composite material prepared by the method according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • High-temperature-resistant wave-transparent silicon nitride fiber-reinforced composite material and preparation method thereof

    CN104261850A

  • Fiber-reinforced silicon nitride composite material and preparation method thereof

    CN112010654A

  • Manufacture method of boron nitride fabric reinforced silicon-boron-nitrogen ceramic-based composite material

    CN102617177A

  • Method for preparing ceramic-based composite material by interface-layer-free process

    CN111892405A

  • Nitride fiber reinforced silicon nitride composite material and preparation method and application thereof

    CN115636681A